2018
DOI: 10.1515/hmbci-2018-0037
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinases in non-alcoholic fatty liver disease and their behavior in liver fibrosis

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a clinical entity of high prevalence in the world characterized by fatty infiltration of liver tissue in the absence of alcohol consumption. The natural history of the disease develops in successive phases reflected in different histological stages, with 10–20% of patients developing liver cirrhosis and fibrosis. Fibrosis is a basic connective tissue lesion defined by the increase of the fibrillary extracellular matrix (ECM) components in a tissue or organ. Matrix m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Toyoda et al [47] reported that mRNA and serum levels of MMP-2 were up-regulated in hepatic steatosis; however, Miele et al [48] found only increased TIMP-1 serum levels. In our laboratory, we recently described a decrease in liver MMP-2 activity in severe fibrosis in comparison to non- to moderate fibrosis stages and no differences in MMP-9 activity in patients with NAFLD [49]. In accordance, Hemman et al [50] previously reported that in activated HSCs, TIMP-1 expression is increased, and concomitantly MMPs activity is reduced, leading to protein accumulation.…”
Section: The Role Of Mmps In Different Tissuessupporting
confidence: 56%
“…Toyoda et al [47] reported that mRNA and serum levels of MMP-2 were up-regulated in hepatic steatosis; however, Miele et al [48] found only increased TIMP-1 serum levels. In our laboratory, we recently described a decrease in liver MMP-2 activity in severe fibrosis in comparison to non- to moderate fibrosis stages and no differences in MMP-9 activity in patients with NAFLD [49]. In accordance, Hemman et al [50] previously reported that in activated HSCs, TIMP-1 expression is increased, and concomitantly MMPs activity is reduced, leading to protein accumulation.…”
Section: The Role Of Mmps In Different Tissuessupporting
confidence: 56%
“…MMP2 and MMP9 are gelatinases responsible for the degradation of extracellular matrix (ECM) proteins which play a key role in the pathogenesis of NAFLD, steatosis, fibrosis, and cirrhosis (Theret et al., 1999). The expression and proteolytic activity of MMP2 and MMP9 are closely regulated by the endogenous activator MT1‐MMP and the inhibitors TIMP1 and TIMP2 (Barchuk et al., 2018). Our findings indicated that MTO attenuates HFD‐induced hepatic fibrosis by reduction of MMP2, MMP9, and MT1‐MMP expressions in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…[ 86 , 87 ]. Thus, activation of TIMPs causes an alteration of the balance between metalloproteinases and their inhibitors, resulting in the deposition and impairment of the ECM architecture [ 88 ]. However, an increase in proMMP-2, and also to a lesser extent active MMP-2, suggests a continuous rotation of the active matrix even in advanced liver fibrosis.…”
Section: Ecm In Mafldmentioning
confidence: 99%